APLIKASI MODEL PENGENDALIAN PERSEDIAAN BARANG DENGAN MENGGUNAKAN MICROSOFT VISUAL BASIC.NET - Yulina Yulina; Hermawan Hermawan (Sienna, 2021)
Inventory control is one of the important problems faced by companies at this time. The problem of inventory control becomes so big because in most companies, inventory is a large part or portion listed on the balance sheet. Inventory that is too large or too small in a company can cause problems. Therefore, the use of mathematical approaches to assist decision-making in determining inventory levels and how the inventory control model is converted into the form of an application program. Computer programs have long been the subject of study. In this case, the inventory control model that will be discussed is the Economic Order Quantity Model which is a simple inventory model that aims to determine the amount of each order (Q) so that the Total Annual Relevant Cost (TC) is minimized.